Jet properties in PbPb and pp collisions at root S-NN=5.02 TeV - Sirunyan, A. M. (2018)
Modifications of the properties of jets in PbPb collisions, relative to those in pp collisions, are studied at a nucleon-nucleon center-of-mass energy of,root S-NN = 5.02 TeV via correlations of charged particles with the jet axis in relative pseudorapidity (Delta eta), relative azimuth (Delta phi), and relative angular distance from the jet axis Delta r = root(Delta eta)(2) + (Delta phi)(2). This analysis uses data collected with the CMS detector at the LHC, corresponding to integrated luminosities of 404 mu b(-1) and 27.4 pb(-1) for PbPb and pp collisions, respectively. Charged particle number densities, jet fragmentation functions, and jet shapes are presented as a function of PbPb collision centrality and charged-particle track transverse momentum, providing a differential description of jet modifications due to interactions with the quark gluon plasma.